Manual deep anterior lamellar keratoplasty after partial unintentional full-thickness trephination. Issue 2 (March 2021) - Sarnicola, Enrica; Sarnicola, Caterina; Cheung, Albert Y; Panico, Edoardo; Panico, Claudio; Sarnicola, Vincenzo
Purpose: The aim of this study was to describe a surgical technique to perform deep anterior lamellar keratoplasty (DALK) despite inadvertent full thickness trephination in one quadrant. Methods: Case report of a 19-year-old boy who underwent DALK for visually significant post-infectious stromal scar in his left eye. An unintentional full thickness trephination occurred in the upper-nasal quadrant at the beginning of the surgery. After suturing the perforated area, manual DALK was performed, and an air bubble was left in the anterior chamber. Evaluated outcomes included best spectacle corrected visual acuity (BSCVA), residual recipient bed thickness, endothelial cell count (ECC), graft clarity, rejection, and presence/absence of double anterior chamber. Results: The surgery was completed without any further complications. No double anterior chamber or Urrets–Zavalia syndrome was observed on the first postoperative day. Mean residual recipient bed thickness was 72 μm and regular. ECC was 2446 cell/mm 2 . BSCVA at 18 months of follow-up was 0.9. There were no episodes of rejection, and the graft remained clear at the last follow-up (4 years). Conclusion: Inadvertent partial full thickness trephination of the recipient cornea is a largely preventable but possible complication during DALK. Penetrating keratoplasty conversion can be avoided by performing a manual dissection DALK.